Population Dynamics of Banteng, Buffalo and Deer in Bekol Savannah, Baluran National Park - SUHADI SUHADI (Biodiversitas Journal of Biological Diversity, 2009)
Baluran National Park give contribution at regional development to draw tourist and fascination provided is savannah in area. Savannah circumstance, forest, landscape, climate, vegetation and wild animal is represent experienced attraction. Research method use population dynamics perception of banteng, buffalo and deer in savannah of Bekol year 2004 and year 2005 as primary data, while secondary data year population dynamics 2003, 2004, and year 2005 outside savannah of Bekol, year population dynamics 2003 in savannah of Bekol. Secondary data obtained from daily report of Controller ecosystem Forest Worker animal discovery Baluran National Park from Section Bekol. Research location of outside savannah Bekol were Balanan, Perengan, Bitakol, Karangtekok, Pandean, Pondok jaran, Bama, Curah uling, Gunung Montor, Lempuyang, Bilik, Batangan, Labuhan Merak, Kramat, Semiang, Sirokoh, Lemah bang, Gunung Krasak, and Glengseran. The populations of banteng and buffalo in the savannah were unstable compared to the populations of them outside Bekol savannah. The populations of banteng and buffalo in Bekol savannah decreased, whereas the populations of them outside the Bekol savannah increased. The population of deer in Bekol savannah in 2004 was better than population of 2003, 2005, and 2006, whereas the population of deer outside Bekol savannah in 2006 increase significantly. The populations of banteng, buffalo, and deer decreased from year to year, in which the reductions of banteng and buffalo populations were obviously significant.Key words: banteng, buffalo, deer, Bekol savannah, Baluran National Park.